Catalytic esterification of palm-based lauric acid diethylene glycol via microwave heating / Noor Azeerah Abas - Noor Azeerah , Abas (2020)
Diethylene glycol esters of fatty acids are mixtures of diethylene glycol mono- and di-esters of saturated and unsaturated fatty acids derived from edible oils and fats. The products are produced either by direct esterification of diethylene glycol with fatty acids or by transesterification of diethylene glycol with oils or fats. This study involved in maximizing the conversion of lauric acid to glycol ester via esterification with diethylene glycol, aided by calcined Zn-Mg-Al catalyst in a 250-ml reactor using both conventional and microwave heating. Preliminary catalytic screening involving tin (II) oxalate, Amberlyst-15 and calcined Zn-Mg-Al catalysts in esterification of lauric acid and diethylene glycol via microwave heating resulted 65.4%, 31.6% and 95.4% of lauric acid being converted, respectively. In addition, conversions obtained from the solid acid catalysts appeared to be higher than autocatalytic esterification of only 15.8%. The optimum operating condition for esterification via microwave heating was established at 190 oC, 2:1.3 mole ratio of lauric acid to diethylene glycol with 5% of catalyst dosage for 90 min. Calcined Zn-Mg-Al catalyst under optimised condition gives 98.2% of lauric acid conversion. The recyclability of the catalysts in the esterification of lauric acid with diethylene glycol were also carried out. It shows that calcined Zn-Mg-Al and tin (II) oxalate both can be used up to six cycles as compared to Amberlyst-15 catalyst that has lost part of its activity after the third cycle. The microwave heating remains attractive for heating catalytic esterification as it accelerates the reaction speed at shorten period of time from 8 hours to 1.5 hours as compared to conventional heating.